Aggregation of poly(N-isopropylacrylamide) homopolymer by Cu2+ and Zn2+: Significance for ratiometric metal ion indicators. (15th November 2020) - Fulton, Luke A.; Seitz, W. Rudolf; Planalp, Roy P.
Graphical abstract: Poly- N -isopropylacrylamide (PNIPAM) supports numerous applications involving aqueous metal ion, but direct interaction between metal ions and the polymer has gone largely unexplored. We show that Cu 2+ and Zn 2+ will bind directly to pure PNIPAM and alter its LCST phase behavior. Notably, binding occurs even without incorporating high affinity metal ligand comonomers. Highlights: Poly- N -isopropylacrylamide (PNIPAM) competes with other ligands for divalent cations. Divalent transition-metal cations have multiple modes of aggregation of acrylamide polymers. Second-order light scattering effectively identifies aggregation of poly- N -isopropylacrylamide. Abstract: Aqueous transition metal dications Cu 2+ and Zn 2+ bind to the amide groups of the responsive polymer poly( N -isopropylacrylamide) (PNIPAm). Ratiometric detection by the response of PNIPAm is based on the effect of metal ion binding to ligands that are copolymerized into PNIPAm. Metal ions bound to copolymerized ligands cause a polarity change that shifts the ratio of coil and globule polymer phases, whereby the coil:globule state is monitored by the FRET process of a pair of fluorophores distributed throughout the polymer. This work shows that aqueous Cu 2+ or Zn 2+ ([M 2+ ] = 2.5 × 10 −2  M to 2.5 × 10 −4  M) cause aggregation of the PNIPAm homopolymer (Mn  = 8400 and 10, 300) in the globule phase above 32 °C, as determined by second-order and dynamic light-scattering. Conditional formation constants (pH 6.3) for Cu 2+ binding PNIPAm were measured as log Kc  = 2.64 ± 0.07 and 4.02 ± 0.05 for PNIPAm concentrations of 1 mg/mL and 0.05 mg/mL, respectively. The interaction of Cu 2+ and Zn 2+ with PNIPAm is therefore in competition with the copolymerized ligands and when detecting millimolar to high micromolar concentrations, this interaction poses a potential interference to metal ion detection. Several aggregation processes are implicated based on Cu 2+ or Zn 2+ from 8 × 10 −5 to 2.5 × 10 −2  M. These processes are fully reversible by reducing the sample temperature.